On the Dynamics of Interstate Migration: Migration Costs and Self-Selection - Christian Bayer; Falko Juessen (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 2006)
This paper develops a tractable dynamic microeconomic model of migration decisions that is aggregated to describe the behavior of interregional migration. Our structural approach allows us to deal with dynamic self-selection problems that arise from the endogeneity of location choice and the persistency of migration incentives. Keeping track of the distribution of migration incentives over time has important consequences, because the dynamics of this distribution influences the estimation of structural parameters, such as migration costs. For US interstate migration, we obtain a cost estimate of somewhat less than one-half of an average annual household income. This is substantially less than the migration costs estimated by previous studies. We attribute this dierence to the treatment of the dynamic self-selection problem.
Keywords: C20; R23; C61; J61; 519; Dynamic self-selection; migration; indirect inference